Some fuzzy common fixed point theorems using common limit in the range property with an application - Bhardwaj Ved Prakash; Wadhwa Kamal (Mathematica Moravica)
In the present paper, we prove some common fixed point theorems for mappings satisfying common limit in the range property in M-fuzzy metric space. Further, we prove fixed point theorem for ph-contractive conditions in aforesaid spaces with the illustration of an example. As an application of our result, we study the existence and uniqueness of the solution of integral equation (Volterra integral equations of the second kind) with instances.